Loving thy work: developing a measure of work passion. Issue 1 (2nd January 2020) - Chen, Patricia; Lee, Fiona; Lim, Sandy
ABSTRACT: Passion for work has become increasingly valued, as reflected by its ubiquity in popular and empirical discourse. Yet we lack scientific consensus on the definition of work passion, and a reliable, well-validated measure of work passion that is relevant to workers across various vocations. In this paper, we identified and integrated key themes from existing scientific conceptualizations into a precise definition: Passion for work means to strongly identify with a line of work that one feels motivated to engage in and derives positive affect from doing. We developed a 10-item Work Passion (WP) scale, which we tested across multiple studies with a total of 858 adults, including working adults from two different English-speaking cultural backgrounds (i.e., United States and Singapore), and a two-wave study of employees from various vocations. Our results showed that work passion is associated with a host of beneficial outcomes, including greater career commitment, lower levels of job burnout, less work-home conflict, and fewer physical symptoms. Our research (1) provides an integrated definition of work passion, (2) offers a reliable, cross-culturally tested scale, and (3) highlights important implications for work outcomes associated with being passionate towards one's line of work.